Global, regional, and national burden of nutritional deficiencies spanning from 1990 to 2021, with a focus on the impacts observed during the COVID-19 pandemic - Zhang, Yue-Yang; Chen, Bing-Xue; Wan, Qin (Frontiers in Nutrition, 2025)
BackgroundThe United Nations has recognized nutritional deficiencies as a critical health issue that necessitates urgent eradication. This study aimed to provide a comprehensive analysis of the spatial distribution and temporal trends of the global disease burden associated with nutritional deficiencies and their four subtypes from 1990 to 2021, with a particular focus on the impact of the COVID-19 pandemic.MethodsThis study primarily employs the most recent data from the Global Burden of Disease (GBD) 2021 to conduct a thorough analysis of the distribution trends of incidence, mortality, and disability-adjusted life years (DALYs) associated with nutritional deficiencies and their four subtypes from 1990 to 2021, incorporating detailed subgroup analyses categorized by sex, age, and region. In comparison to the GBD 2019, the GBD 2021 update places a particular emphasis on supplementing disease burden data for the period of the COVID-19 pandemic (2019–2021). Furthermore, this study investigates the primary risk factors contributing to disability-adjusted life years (DALYs) linked to nutritional deficiencies.ResultsBetween 1990 and 2021, the global burden of nutritional deficiencies experienced a substantial decline, evidenced by a 54.9% reduction in the age-standardized incidence rate (ASIR), a 72.2% decrease in the age-standardized death rate (ASDR), and a 51.9% reduction in the age-standardized DALY rate. However, it is noteworthy that the burden of iodine deficiency (ASIR: 137.72 vs. 75.49; Age-standardized DALY rate: 35.43 vs. 19.98) and dietary iron deficiency (Age-standardized DALY rate: 597.97 vs. 253.05) is considerably greater in women than in men. Moreover, in regions characterized by a low social demographic index (SDI) and lower income levels, the burden of diseases associated with nutritional deficiencies remains substantial. In contrast, the COVID-19 pandemic has not markedly changed the epidemiological profile of nutritional deficiencies compared to the pre-2019 period, and the global burden of nutritional deficiencies has continued its gradual decline.ConclusionsDespite a decline in the global burden of nutritional deficiencies over time, significant disparities related to gender, region, and age persist. Fortunately, the COVID-19 pandemic has had a relatively limited impact on the global burden of nutritional deficiencies. Healthcare institutions must formulate more targeted strategies aimed at alleviating the adverse effects of nutritional deficiencies on global public health.